Exploring the feasibility and utility of exome‐scale tumour sequencing in a clinical setting. Issue 7 (8th July 2018) - Lee, Belinda; Tran, Ben; Hsu, Arthur L.; Taylor, Graham R.; Fox, Stephen B.; Fellowes, Andrew; Marquis, Renata; Mooi, Jennifer; Desai, Jayesh; Doig, Ken; Ekert, Paul; Gaff, Clara; et al.
Abstract: Background: Technology has progressed from single gene panel to large‐scale genomic sequencing. This is raising expectations from clinicians and patients alike. The utility and performance of this technology in a clinical setting needs to be evaluated. Aim: This pilot study investigated the feasibility of using exome‐scale sequencing (ESS) to identify molecular drivers within cancers in real‐time for Precision Oncology in the clinic. Methods: Between March 2014 and March 2015, the Victorian Comprehensive Cancer Centre Alliance explored the feasibility and utility of ESS in a pilot study. DNA extracted from the tumour specimens underwent both ESS and targeted 'hotspot' sequencing (TS). Blood was taken for germline analysis. A multi‐disciplinary molecular tumour board determined the clinical relevance of identified mutations; in particular, whether they were 'actionable' and/or 'druggable'. Results: Of 23 patients screened, 15 (65%) met the tissue requirements for genomic analysis. TS and ESS were successful in all cases. ESS identified pathogenic somatic variants in 73% (11/15 cases) versus 53% (8/15 cases) using TS. Clinically focused ESS identified 63 variants, consisting of 30 somatic variants (including all 13 identified by TS) and 33 germline variants. Overall, there were 48 unique variants. ESS had a clinical impact in 53% (8/15 cases); 47% (7/15 cases) were referred to the familial cancer clinic, and 'druggable' targets were identified in 53% (8/15 cases). Conclusion: ESS of tumour DNA impacted clinical decision‐making in 53%, with 20% more pathogenic variants identified through ESS than TS. The identification of germline variants in 47% was an unexpected finding.